Ethnic capital and self-employment: A spatially autoregressive network approach - Xingang Wang; Sholeh A. Maani (IZA Journal of Migration, 2014)
Immigrants experience substantial disadvantages in employment in the host country. "Ethnic capital" (e.g. the ethnic network) is argued to provide a niche for immigrants. Previous international studies adopt either ethnic concentration or language as proxy for immigrants' network in host country. In this paper we introduce a new "spatial autoregressive network approach" to construct a dynamic network variable from micro-data to capture the effects of social and resource networks for immigrants. This approach allows each individual's self-employment decision to be geographically and ethnically correlated with that of other individuals. We further show that there are three advantages of this approach: it captures a more accurate effect of networks; it provides a better estimation of the impact of other socio-economic variables on self-employment; and it provides a better data fit. The empirical findings of this study strongly suggest that ethnic capital plays a vital role in relation to immigrants' self-employment decisions.
Keywords: J23; J61; Z13; 330; Ethnic capital; Ethnic network; Ethnic concentration; Spatial approach; Immigrant; Self-employment